Pain and stress after vaginal delivery: characteristics at hospital discharge and associations with parity. (17th August 2020) - Zanardo, Vincenzo; Parotto, Matteo; Manghina, Valeria; Giliberti, Lara; Volpe, Francesca; Severino, Lorenzo; Straface, Gianluca
Abstract: The objective of this study was to characterise pre-discharge maternal pain and stress severity after vaginal delivery and associations with parity. This is a descriptive analysis with 148 women in the early post-partum period (84 primiparae and 64 secondiparae) after vaginal delivery. Pain and stress were measured by McGill Pain Questionnaire (MGPQ) and by the Psychological Stress Measure (PSM). Vaginal delivery in primiparae women was associated with MGPQ, significantly higher pain scores. Sensorial, affective and mixed pain descriptive categories were also significantly higher. Pain location involved lower abdomen, vagina and perianal area. In addition, their PSM showed a significantly higher 'Sense of effort and confusion' subscale scores. In conclusion, this study provides important information on the quality of care implications of hospital-to-home discharge practices in puerperae after vaginal delivery, a critical time characterised by qualitatively and quantitatively high pain and stress in primiparae. Impact statement: What is already known on this subject? Pain and fatigue are the most common problems reported by women in the early postpartum period. What the results of this study add? Primiparae who delivered vaginally presented at the time of hospital-to-home discharge significantly higher pain and stress, as compared to secondiparae. Pain involved lower abdomen, vagina and perianal area, whereas the stress was quantitatively higher in the 'sense of effort and confusion'. What the implications are of these findings for clinical practice and/or further research? Awareness of problematic pain and stress associations with parity may offer the opportunity to better support puerperae to develop maternal orientation and adjust to motherhood.